Online learning and assessment during the Covid-19 pandemic: exploring the impact on undergraduate student well-being. Issue 3 (3rd April 2023) - Slack, Hannah R.; Priestley, Michael
Abstract: Where traditional learning and assessment approaches have previously been found to negatively impact on student well-being, the Covid-19 pandemic provided a novel opportunity to explore alternative online learning and assessment conditions conducive to student well-being and academic performance as part of a whole university strategy. To this end, the present study employed a mixed-methodological approach using a quantitative survey and 10 focus groups to examine the impact of online learning and assessment on the undergraduate students' well-being. The findings indicate that whilst some students report online learning and assessment to require more effort in comparison to traditional methods, other students value the increased flexibility afforded by online learning and assessment. It is recommended that academic staff scaffold online learning and assessment methods in the curriculum.